(untitled) (Journal of the College of Basic Education, 2023)
The theatrical text and its role in activating educational values through puppet performances being the closest to the child’s mind, which may interfere greatly with his psychology and behavior as an individual and his influence in society, which requires an actual study of the child’s behavior through which the objectives of the puppet theater are achieved, which require the study of all influences, problems and factors Which contribute to the success of this task and its role in activating the purposeful values, based on the foregoing, the research came out with the following question: What are the educational values and how does it affect the texts of the puppet theater? The current research aims to identify the educational values in the puppet theater texts. The research community included (4) theatrical texts written by (Dr. Hussein Ali Harf), which achieve artistic educational values. The research sample was determined by one text entitled (Union of Birds), and the sample was chosen based on the opinion of experts specialized in the field of theatrical composition, as it contains educational values. The research came out with a set of results, which are: As it included (group unity, family love, cooperation, honesty, obedience, comfort, excitement, fun, happiness, achievement, strength, speaking, intelligence, food). The most important conclusions are: Social values: (adverb and kindness, tolerance, generosity and giving, family love) do not exist in the conflict formula within the play. The most important recommendations are: Emphasis on the basic educational values that build personality in a way that reflects positively on the system of social values and other educational values.